Mapping the post-fire resilience of Mediterranean pine forests: the case of Sounion national park, Greece - Arianoutsou M.; Kazanis D.; Varela V. (Proceedings of the international workshop MEDPINE 3: conservation, regeneration and restoration of Mediterranean pines and their ecosystems, 2007)
Given the heterogeneity of the Mediterranean landscapes and the restriction in personnel and resources, the identification of patches requiring the application of specific rehabilitation measures due to low post-fire resilience becomes important. The methodology proposed in this paper is acting towards this direction. The research has been carried out in Sounion National Park, a site of ecological and aesthetic value, given its proximity to Athens metropolitan area. A large part of the Pinus halepensis forest of the Park has experienced two overlapping fires in summer 1985 and summer 2000. By definition, all patches burned twice are considered as low resilient to fire. On this biological background, the effect of landscape heterogeneity, by means of soil type and slope inclination, on the most important parameters defining post-fire resilience was studied and mapped. This process is by itself an intriguing objective. In this work, the biological parameters used as bioindicators of the landscape resilience are pine saplings density and woody vegetation cover.
Proceedings of the International Workshop, 2005/09/26-30, Bari (Italy)